KEBIJAKAN MAKAN BERGIZI GRATIS ATAU SUARA UNTUK PEMILU?: KAJIAN LITERATUR DENGAN PENDEKATAN ANALISIS WACANA KRITIS - Rawis, Sintia Maria (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
The narrative of "free nutritious meals" has emerged as a flagship policy within the broader discourse of social welfare in Indonesia. This policy has gained significant public attention, particularly in the context of social justice and state responsibility. This study is a literature review utilizing the Critical Discourse Analysis (CDA) approach, drawing on the theoretical frameworks developed by Norman Fairclough and Teun A. van Dijk. The analysis focuses on the discourse construction of this policy by examining the role of political actors, media coverage, and relevant academic literature. The study finds that the narrative of "free nutritious meals" is not solely framed as a solution to nutritional and welfare issues, but also functions as a rhetorical instrument to construct a leadership image and garner political support. This discourse reveals a hidden power dynamic in which critical structural issues—such as economic inequality, food system sustainability, and public engagement—are often overlooked. The study highlights the importance of critically reading public policies, so they do not merely serve as tools of political legitimacy, but genuinely aim to promote social justice. It also recommends the need for increased critical awareness in evaluating policies, especially those claiming to be socially sustainable and justice-oriented.